If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-(4y+2)-(-3y-8)=6
We simplify the equation to the form, which is simple to understand
-(4y+2)-(-3y-8)=6
Remove unnecessary parentheses
-4y-2-(-3y-8)=6
Remove unnecessary parentheses
-4y-2+3y+8=6
We move all terms containing y to the left and all other terms to the right.
-4y+3y=+6+2-8
We simplify left and right side of the equation.
-1y=0
We divide both sides of the equation by -1 to get y.
y=-0
| 6x+5=7x-9 | | -4+5= | | y^2+10y+25=2y^2+11y-5 | | 21+(-3)(7)= | | 3-6=7 | | 6(3x-8)=3(6x+2) | | -2(8x-5)+2x=4(x+5) | | (-24)+(-3)*(-2)=-4 | | 9y=4(x+6) | | 3ln(2x)=-6 | | 10m+0.09=16m+0.07 | | 8+5x-5=9x+11-5x | | 22-6[(-3)+(-7)]-5=-43 | | -2(4n+5)=8 | | x^3-6x^2+13x-20=0 | | x/9=-25 | | x^3+7x^2+25x+39=0 | | 3x-5-6x=31 | | 275=150(t)-16t^2 | | 4z=-8 | | 3x^2-16x-2=0 | | 3(x-5)=-18 | | -9(3b+3)+(28b-4)=0 | | 20+B=2B-30 | | 8n+3n=12n+9 | | 2x^3-11x^2+19x-10=0 | | -x^2+11x-28=0 | | 3(2y-4)=9 | | 7x-9=6x+5 | | 3.9q-1.3-5.3q=2.4q-5.5 | | 24=n+N | | 12x^3-27xy^2= |